Phenology of Cinnamomum cullilawan - Rima Herlina Siburian (Median : Jurnal Ilmu Ilmu Eksakta, 2022)
Abstract Cinnamomum cullilawan is one type of forest plants that is included in the type of aromatic plants. The purpose of this study was to determine the flowering development process as a basicÂ  information for the development and the breeding of this plant. The method used in this research was a descriptive method. The results of the observations indicated that the process of flowering C. cullilawan can be grouped into three major parts: the stage of initiation, budding and flowering, where each stage requires different formation times. At the initiation stage, since the emergence of generative shoots on the armpit until the formation of panicles takes two months. Furthermore, the stage of the appearance of buds at the ends of panicles and the formation of reproduction of flowers required two months period. After that the flowers will break slightly and then the petals will turn black and fall in the second week, after the flower process has blossomed.